Desafios ao planeamento dos territórios suburbanos: o planeamento do desenvolvimento territorial na Amadora - João Cabral; Cristina Delgado Henriques (Cidades, Comunidades e Território)
Transformations in processes and patterns of suburbanization in metropolitan areas have been the subject of study associated with challenges to urban planning. The main objective of the article is to address the challenges of planning suburban territories responding to global trends in terms of urbanization patterns and to a crisis in the regulatory and planning systems. The approach is supported by debates on planetary urbanization and the suburban condition as an object of study applying the concept of territorial development planning (“place-based planning”). The discussion contributed to the construction of an analytical framework of the evolution of the territory of the municipality of Amadora in the Lisbon metropolitan area in its urban and planning dimensions. The analysis of this diverse and complex suburban area illustrates the usefulness and possibilities of an oriented approach to territorial development planning.